Sugar politics in Negros Occidental the dynamics between big landholders and small landholders in Planter's Associations in Silay-Saravia and BISCOM Mill Districts - Francisco, Kristina P. (University of the Philippines in the Visayas, 2005)
This research examined the nature of interaction of planters in the association and mill district level in Silay-Saravia and BISCOM mill districts as major actors in the sugar industry, and their dealings with the SRA (represents the government) in promoting their interests. This research also inqquired into how the government invitess greater political participation among them as representatives of the private sector. The researcher uutilized primary data from key informants-the planters (one CARP beneficiary and one big planter in each association). The results of the study showed that : (1) big planters, are actively participating in the association and mill district level and are given the privilege to lobby formally in the government through SRS-accredited MDDCs, (2) small planters are only passive and unreceptive participants in the association and mill district level and (3) sugar planters (representing the private sector), and the government are interdepenedetn, inter-reliant and mutually supporting each other.